(untitled) (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2023)
Scleractinian coral such as Lobophyllia corymbosa that reproduce by external fertilization have an extended planktonic phase in their life cycle during which they "drift" in the water column. This life cycle phase is an advantage in itself because it increases the capacity of propagules to disperse far from their place of origin. In this hydrodynamic model study, secondary data on bathymetry and tides for the western monsoon period (represented by November 2017) were input into the Surface Water Modelling System SMS 8.1 to simulate the surface current circulation model. In running this program there are 2 important stages, namely GFGEN (Geometry File Generation) and RMA2 (Resources Management Associates-2). The simulation of surface current direction during the west monsoon, which is the reproductive period of L. corymbosa in Indonesia, shows the complexity and distraction of current vectors that occur in the coastal waters around Sulawesi Island. The model results indicate the possibility of spatial and temporal biological networks forming in waters around Sulawesi. The current patterns forming in Sulawesi waters during the west monsoon tend to circulate from north to south due to the higher volume of water mass originating from the Pacific Ocean flowing to the southern part of Sulawesi which is also the entry point for the Indonesian Throughflow (ITF). The larval dispersion model scenario produced for each location (Manado, Toli-Toli, Palu, Mamuju, Spermonde, Sinjai, Wakatobi, and Luwuk Banggai) tended to follow the water movement patterns, with most propagules leaving the location where they were spawned.